Medicinal chemistry of the myeloid C-type lectin receptors Mincle, Langerin, and DC-SIGN. Issue 12 (27th September 2021) - Cramer, Jonathan
Abstract : This review outlines the current state of research into glycomimetic or drug-like small molecule ligands for the C-type lectin receptors Mincle, Langerin, and DC-SIGN, which have potential applications in vaccine research and anti-infective therapy. Abstract : In their role as pattern-recognition receptors on cells of the innate immune system, myeloid C-type lectin receptors (CLRs) assume important biological functions related to immunity, homeostasis, and cancer. As such, this family of receptors represents an appealing target for therapeutic interventions for modulating the outcome of many pathological processes, in particular related to infectious diseases. This review summarizes the current state of research into glycomimetic or drug-like small molecule ligands for the CLRs Mincle, Langerin, and DC-SIGN, which have potential therapeutic applications in vaccine research and anti-infective therapy.